The Impact of Hazardous Drinking Among Active Duty Military With Posttraumatic Stress Disorder: Does Cognitive Processing Therapy Format Matter?. Issue 1 (19th October 2020) - Straud, Casey L.; Dondanville, Katherine A.; Hale, Willie J.; Wachen, Jennifer S.; Mintz, Jim; Litz, Brett T.; Roache, John D.; Yarvis, Jeffrey S.; Young‐McCaughan, Stacey; Peterson, Alan L.; Resick, Patricia A.; ,
Abstract: This study was a secondary data analysis of clinical trial data collected from 268 active duty U.S. military service members seeking cognitive processing therapy (CPT) for posttraumatic stress disorder (PTSD) at Fort Hood, Texas, related to combat operations following September 11, 2001. Our primary aim was to evaluate changes in PTSD symptom severity and alcohol misuse as a function of baseline hazardous drinking and treatment format (i.e., group or individual). At baseline and posttreatment, PTSD was assessed using the PTSD Symptom Scale–Interview Version and PTSD Checklist for DSM‐5 . Hazardous drinking was categorically defined as an Alcohol Use Disorder Identification Test total score of 8 or higher. Employing intent‐to‐treat, mixed‐effects regression analysis, all groups reported reduced PTSD symptom severity, Hedges' g s = −0.33 to −1.01, except, unexpectedly, nonhazardous drinkers who were randomized to group CPT, Hedges' g = −0.12. Hazardous drinkers who were randomized to individual therapy had larger reductions in PTSD symptoms than nonhazardous drinkers who were randomized to group CPT, Hedges' g = −0.25. Hazardous drinkers also reported significant reductions in alcohol misuse, regardless of treatment format, Hedges' g s = −0.78 to −0.86. This study builds upon an emerging literature suggesting that individuals with PTSD and co‐occurring alcohol use disorder can engage successfully in CPT, which appears to be an appropriate treatment for these individuals whether it is delivered individually or in a group format. However, as a portion of participants remained classified as hazardous drinkers at posttreatment, some individuals may benefit from integrated treatment. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0132.R2_Straud_cantonese Traditional Chinese 現役軍人危險飲酒對創傷後壓力症的影響:認知加工治療形式重要嗎? 摘要 : 這項研究是對從德州胡德堡的268名現役美國軍人中收集的臨床試驗數據進行的二次數據分析, 在2001年9月11日之後的戰鬥行動中, 在德州胡德堡尋求創傷後壓力症(PTSD)的認知加工治療(CPT)。我們的主要目的是評估創傷後壓力症狀嚴重程度和酒精濫用作為基線危險飲酒和治療形式(即群體或個人)的功能變化。在基線和治療後, 使用PTSD症狀量表‐訪談版和DSM‐5的PTSD檢查表對PTSD進行評估。危險飲酒被歸類為酒精使用障礙識別測試總分為8分或更高。採用意向治療、混合效應回歸分析, 所有組別都報告了PTSD症狀嚴重程度的降低, Hedges' gs = ‐0.33至‐1.01, 但意外的是, 被隨機分配到CPT組的非危險性飲酒者, Hedges' g = ‐0.12 。被隨機分配到個人治療的危險飲酒者比被隨機分配到小組CPT的非危險飲酒者在PTSD症狀上有更大的減少, Hedges' g =‐0.25 。無論治療形式如何, 危險性飲酒者還報告了酒精濫用的顯著減少, Hedges' g s = ‐0.78到‐0.86 。這項研究建立在一項新興文獻的基礎上, 這些文獻表明, 患有創傷後壓力症(PTSD)和同時發生的酒精使用障礙的個體可以成功地進行CPT, 無論單獨或以小組形式進行治療, 這似乎是對這些人的適當治療。然而, 由於一部分參與者在治療後仍被歸類為危險飲酒者, 一些人可能從綜合治療中受益。 Simplified Chinese 现役军人危险饮酒对创伤后压力症的影响:认知加工治疗形式重要吗? 摘要 : 这项研究是对从德州胡德堡的268名现役美国军人中收集的临床试验数据进行的二次数据分析, 在2001年9月11日之后的战斗行动中, 在德州胡德堡寻求创伤后压力症(PTSD)的认知加工治疗(CPT)。我们的主要目的是评估创伤后压力症状严重程度和酒精滥用作为基线危险饮酒和治疗形式(即群体或个人)的功能变化。在基线和治疗后, 使用PTSD症状量表‐访谈版和DSM‐5的PTSD检查表对PTSD进行评估。危险饮酒被归类为酒精使用障碍识别测试总分为8分或更高。采用意向治疗、混合效应回归分析, 所有组别都报告了PTSD症状严重程度的降低, Hedges' gs = ‐0.33至‐1.01, 但意外的是, 被随机分配到CPT组的非危险性饮酒者, Hedges' g = ‐0.12 。被随机分配到个人治疗的危险饮酒者比被随机分配到小组CPT的非危险饮酒者在PTSD症状上有更大的减少, Hedges' g =‐0.25 。无论治疗形式如何, 危险性饮酒者还报告了酒精滥用的显著减少, Hedges' g s = ‐0.78到‐0.86 。这项研究建立在一项新兴文献的基础上, 这些文献表明, 患有创伤后压力症(PTSD)和同时发生的酒精使用障碍的个体可以成功地进行CPT, 无论单独或以小组形式进行治疗, 这似乎是对这些人的适当治疗。然而, 由于一部分参与者在治疗后仍被归类为危险饮酒者, 一些人可能从综合治疗中受益。